Construction of an Islamic Studies Curriculum Based on Religious Moderation in Higher Education Institutions (EDUKASIA, 2022)
This study aims to explain the Islamic studies curriculum based on religious moderation in higher education institutions (HEIs). In developing an Islamic studies curriculum, it is necessary to have an integrated concept between goals, materials, strategies, and evaluation. Curriculum development also needs to pay attention to supervision and cooperation with the Ministry of Religion and partnerships with religious leaders. The focus of Islamic studies based on religious moderation in HEIs is the Islamic religious education course. This literature research used primary data from books on the HEIs curriculum and learning Islam in HEIs. Meanwhile, secondary data sources came from books and articles related to the Islamic studies curriculum in HEIs. The findings revealed that for the measurable construction of Islamic studies curriculum in HEIs, it should fulfill at least three aspects: (1) normative curriculum construction, (2) current facts curriculum construction, and (3) curriculum reconstruction (rearrangement). This research further contributes to HEIs in compiling Islamic studies curricula to create students with a moderate attitude.